2019
DOI: 10.1002/lary.28060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total and partial ossicular replacement prostheses in patients with an intact stapes suprastructure

Abstract: Objectives To compare the results of ossiculoplasty with two different partial ossicular replacement prostheses (PORP) to ossiculoplasty with a total ossicular replacement prosthesis (TORP) in patients with an intact stapes suprastructure. Methods All patients required primary or revision surgery for chronic middle ear disease and ossicular reconstruction with either a PORP or a TORP, as well as a with an intact stapes suprastructure. In total, 141 patients receiving classic tympanoplasty with PORP (N = 92), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
3
3
0
Order By: Relevance
“…It is hypothesized that the results of hearing restoration are comparable independently from the size of the cholesteatoma. This finding is well in accordance to existing studies demonstrating that even after largely extended cholesteatoma, a satisfying hearing restoration can be achieved [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is hypothesized that the results of hearing restoration are comparable independently from the size of the cholesteatoma. This finding is well in accordance to existing studies demonstrating that even after largely extended cholesteatoma, a satisfying hearing restoration can be achieved [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is hypothesized that the results of hearing restoration are comparable independently from the size of the cholesteatoma. This finding is well in accordance to existing studies demonstrating that even after largely extended cholesteatoma, a satisfying hearing restoration can be achieved [33]. Additionally, this study showed that a poorer status of the ossicular chain is associated with poorer pre-and postoperative hearing thresholds confirming earlier investigations on this concern [17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of course, the presence of cholesteatoma in patients with tympanosclerosis complicates the surgery. However, we believe that, with appropriate surgical treatment, it should not hinder achieving hearing gain, as also reported by Weiss et al [19].…”
Section: Discussionsupporting
confidence: 77%
“…The surgical technique of ossiculoplasty performed using total ossicular replacement prostheses (TORP) is considered when the patient doesn't have malleus, incus, and stapes supra structures. It is commonly operated using interposed cartilage between the prostheses device and the tympanic membrane [ 3 ]. As a result, the use of cartilage graft has been shown to decrease surgery failure and prostheses extrusion [ 1 , 4 ].…”
Section: Introduction and Importancementioning
confidence: 99%